2013
DOI: 10.1177/0022034513495239
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Periodontal Health in Older Men

Abstract: Vitamin D, an anti-inflammatory mediator, has potential benefits for physical and oral health. Although it is produced endogenously, some individuals have a greater need for dietary and supplemental sources. This repeated-measures crosssectional study assessed associations between total vitamin D intake and periodontal health in older men. Participants were 562 members of the Department of Veterans Affairs Dental Longitudinal Study, mean age 62.9 years, who were examined 1 to 4 times between 1986 and 1998. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 26 publications
3
82
1
2
Order By: Relevance
“…An inverse relationship between periodontal disease indicators and vitamin D levels was demonstrated in a study by Alshouibi et al (2013), where the total vitamin D intake C800 IU/day was associated with lower odds of severe periodontal disease and moderate-to-severe alveolar bone loss compared with an intake \400 IU/day. It was also observed that low serum levels of vitamin D adversely affect the healing process in post-operative wounds after periodontal surgical procedures.…”
Section: Periodontitismentioning
confidence: 92%
“…An inverse relationship between periodontal disease indicators and vitamin D levels was demonstrated in a study by Alshouibi et al (2013), where the total vitamin D intake C800 IU/day was associated with lower odds of severe periodontal disease and moderate-to-severe alveolar bone loss compared with an intake \400 IU/day. It was also observed that low serum levels of vitamin D adversely affect the healing process in post-operative wounds after periodontal surgical procedures.…”
Section: Periodontitismentioning
confidence: 92%
“…Long-term topical application of rCoQ10 onto the gingiva of aging rats inhibited oxidative DNA damage, expression of genes encoding inflammatory mediators including components of the Nod-like receptor protein (NLRP)3 inflammasome, and osteoclastogenesis, in contrast to control treatment with vehicle only [74]. Vitamin D is a powerful natural antioxidant and a recent study showed a correlation between vitamin D intake (≥ 800 IU) and protection against periodontal disease progression in relatively old age (men with an average age of 63) [75]. However, it should be noted that vitamin D has pleiotropic effects in immune regulation and inflammation [76] including regulation of local immunity at the periodontal tissue [77].…”
Section: Inflamm-aging and Periodontitismentioning
confidence: 99%
“…Most, 7‐12 although not all, 13 previous cross‐sectional and case‐control studies have supported vitamin D status as a potential modifiable risk factor for periodontal disease. Few studies 14‐18 have examined associations between vitamin D status and periodontal disease measures taken over time. Garcia et al 14 conducted a 1‐year study of 51 patients with moderate‐to‐severe chronic periodontal disease attending a periodontal disease maintenance program.…”
mentioning
confidence: 99%
“…In a larger epidemiologic study of 550 men, Krall 15 found no association between self‐reported baseline intake of vitamin D from foods and supplements and 7‐year progression in alveolar bone loss. In another study of 562 men, Alshouibi et al 17 used a repeated‐measures cross‐sectional design to examine associations between vitamin D intake and periodontal disease collected one to four times from 1986 to 1998. Vitamin D intake was associated with lower odds of moderate‐to‐severe periodontal disease.…”
mentioning
confidence: 99%